Hydroxychloroquine is effective, and consistently so used early, for Covid-19: A systematic review (2020)
Introduction Hydroxychloroquine (HCQ) has shown efficacy against COVID-19 in some but not all studies. We hypothesized that systematic review would show HCQ to be: effective against COVID-19, more effective when used earlier, not associated with worsening, and safe. Methods We searched PubMed, Cochrane, EmBase, Google Scholar, and Google for all reports on hydroxychloroquine as a treatment for COVID-19 patients. This included pre-prints and preliminary reports on larger COVID-19 studies. We examined the studies for efficacy, time of administration and safety. Results HCQ was found consistently effective against COVID-19 when used early, in the outpatient setting. It was found overall effective also including inpatient studies. No unbiased study found worse outcomes with HCQ use. No mortality or serious safety adverse event was found Conclusions HCQ is consistently effective against COVID-19 when used early in the outpatient setting, it is overall effective against COVID-19, it has not produced worsening, it is safe.